Challenges of Iran's Legislative Criminal Policy at the Beginning of the Crime - Pouya Shirani; Sina Gholfi (پژوهشهای حقوقی, 2023)
Each country has a determined response system for committing a crime. And in the Islamic Penal Code, the punishment for committing a crime is explicitly stated in Article 122. Indeed, this action helps to the coherence of the rulings. However, despite this positive approach, this system has faced gaps in crimes with multiple punishments and has presented problems to judges; For example, in a crime such as combat, which has diverse and facultative penalties, It is not clear based on which paragraph of Article 122 of the Islamic Penal Code the judge should determine the punishment at the beginning of this crime. Penalties prescribed for combat do not fit into any of the mentioned articles, such as negation. There are different perspectives to address this issue. These notions can be divided into three main approaches, encompassing the judge's discretion that is the criterion for imposing the most severe or mild legal punishment. Examination of the existing opinions shows that the application of each will have advantages and disadvantages. In this article, we have studied and analyzed these approaches through the interpretative analytical method. Thus, in crimes that the trial took the legislature of any crimes, this discretion is also true at the beginning. However, in order for judges to be less likely to issue dissenting verdicts, they should pay attention to the type of crime committed and the policy that is enacted from the set of criminal rules governing those crimes.